2006
DOI: 10.1016/j.energy.2005.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic prospects of small-scale membrane reactors in a future hydrogen-fuelled transportation sector

Abstract: The membrane reactor is a novel technology for the production of hydrogen from natural gas. It promises economic small-scale hydrogen production, e.g. at refuelling stations and has the potential of inexpensive CO 2 separation. Four configurations of the membrane reactor have been modelled with Aspen plus to determine its thermodynamic and economic prospects. Overall energy efficiency is 84% HHV without H 2 compression (78% with compression up to 482 bar). The modelling results also indicate that by using a sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 60 publications
3
34
0
Order By: Relevance
“…Their results demonstrated that the Pd metal cost is insignificant when the thickness reaches approximately 5 mm. This is in agreement with other studies [13], and a logical result that also applies for small scale hydrogen production [14]. Figure 7.2 shows schematically three sequential WGS reactors and separation processes [15] after reforming of natural gas in low pressure hydrogen production.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Their results demonstrated that the Pd metal cost is insignificant when the thickness reaches approximately 5 mm. This is in agreement with other studies [13], and a logical result that also applies for small scale hydrogen production [14]. Figure 7.2 shows schematically three sequential WGS reactors and separation processes [15] after reforming of natural gas in low pressure hydrogen production.…”
Section: Introductionsupporting
confidence: 89%
“…SR-MR and WGS-MR are also technologies for the production of hydrogen on a smaller scale, for example for local filling stations [14,16]. This will not be further discussed in this chapter.…”
Section: Introductionmentioning
confidence: 99%
“…Decentralised electricity and hydrogen production is generally not considered due to the relatively high costs of CCS at such scales. Advanced concepts using fuel cells and membranes, however, offer the potential for low-cost CO 2 capture at relatively small scales [28]. Decentralised electricity production with CCS is of particular interest for the Netherlands given the large share of decentralised CHP units (circa 5 GW e of total installed capacity near 20 GW e in 2003) [29].…”
Section: Technologiesmentioning
confidence: 99%
“…For centrally produced hydrogen two modes of transportation are assessed; gaseous pipeline and liquid truck transport (Table 3). For the pipeline a large distribution pipeline, pressure 60 bar 16 over 13 Electricity and natural gas prices supplied from the grid are based on prices for small industrial users in the EU which correspond to the scales used in the analysis in this paper [28].…”
Section: Hydrogen Transportmentioning
confidence: 99%